TLS 1.3 Handshake Analyzer - Giron, Alexandre Augusto; Schardong, Frederico; Custódio, Ricardo (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg_estendido.2022.226725, 2022)
The Transport Layer Security (TLS) protocol is the de facto standard for global Internet security. Despite its performance and security improvements over previous versions, there are still challenges regarding user privacy and security against future quantum attackers. Although there are several initiatives to address these challenges, there is no specialized tool to analyze these new features. This paper presents the TLS 1.3 Handshake Analyzer, a tool for security and performance analysis of TLS connections. Users can obtain security information about their connections, and server administrators can use it to validate the effects of TLS in their network applications, such as handshake timings and the sizes of transferred cryptographic objects.